ChemInform Abstract: Enantioselective Organocatalytic Domino Synthesis of Tetrahydropyridin‐2‐ols. Issue 3 (22nd January 2013) - Wan, Jie‐Ping; Loh, Charles C. J.; Pan, Fangfang; Enders, Dieter
Abstract A series of tetrahydropyridin‐2‐ols (III) is obtained by a Michael addition‐hemiaminalization reaction sequence of enaminones (I) with enals (II).